2007
DOI: 10.1074/jbc.m703871200
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Helix-Turn-Helix Protease Inhibitory Motif in a Novel Trypsin Inhibitor from Seeds of Veronica (Veronica hederifolia L.)

Abstract: The storage tissues of many plants contain protease inhibitors that are believed to play an important role in defending the plant from invasion by pests and pathogens. These proteinaceous inhibitor molecules belong to a number of structurally distinct families. We describe here the isolation, purification, initial inhibitory properties, and three-dimensional structure of a novel trypsin inhibitor from seeds of Veronica hederifolia (VhTI). The VhTI peptide inhibits trypsin with a submicromolar apparent K i and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 34 publications
4
58
0
5
Order By: Relevance
“…The cysteine motif of these peptides may therefore be presented as: C1XXXC2-X(n)-C3XXXC4. The same cysteine pattern is shared by AMPs from two other cereals, maize (MBP-1) [15] and barnyard grass Echinochloa crus-galli (EcAMP1) [16], a dicotyledonous plant the Queensland nut Macadamia integrifolia (MiAMP2) [17], trypsin inhibitors from the ivy-leaved speedwell Veronica hederifolia (VhTI) [18] and buckwheat Fagopyrum esculentum (BWI-2b and BWI-2c) [19,20]. Moreover, we established the disulfide connectivity in Tk-AMP-X2, which was found to be identical to that in EcAMP1, VhTI, BWI-2b and BWI-2c.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cysteine motif of these peptides may therefore be presented as: C1XXXC2-X(n)-C3XXXC4. The same cysteine pattern is shared by AMPs from two other cereals, maize (MBP-1) [15] and barnyard grass Echinochloa crus-galli (EcAMP1) [16], a dicotyledonous plant the Queensland nut Macadamia integrifolia (MiAMP2) [17], trypsin inhibitors from the ivy-leaved speedwell Veronica hederifolia (VhTI) [18] and buckwheat Fagopyrum esculentum (BWI-2b and BWI-2c) [19,20]. Moreover, we established the disulfide connectivity in Tk-AMP-X2, which was found to be identical to that in EcAMP1, VhTI, BWI-2b and BWI-2c.…”
Section: Resultsmentioning
confidence: 99%
“…The peptide was cleaved at Met residues by cyanogen bromide, and the resulting mixture was analyzed by MS. Two fragments were identified with molecular masses of 1628 and 1831 Da. The latter corresponds to the middle part of the peptide (residues [9][10][11][12][13][14][15][16][17][18][19][20][21][22] containing the 'inner' Cys 9 -Cys 21 disulfide bond. The former corresponds to the two flanking parts (residues 1-8 and 23-28) held together by the 'outer' Cys 5 -Cys 25 disulfide bond.…”
Section: Resultsmentioning
confidence: 99%
“…At that time no homology with known inhibitors was found. Both the native inhibitor and corresponding especially synthesized peptide have been crystallized and their three-dimensional structures were determined (Conners et al, 2007). It was found that this inhibitor contains an unusual for inhibitors helix-turn-helix proteinase inhibitory motif.…”
Section: Trypsin Inhibitor From Seeds Of Veronica With An Unusual Helmentioning
confidence: 99%
“…Affinity matrices using proteinases (trypsin, chymotrypsin and subtilisin) or proteinase inhibitors immobilized on CNBr-activated Sepharose or acrylamide or agarose gels were used for purification of proteinase inhibitors from plants and proteinases from insects (Conners et al, 2007;Konarev 1986a, Konarev et al, 2000, 2002a, 2008, 2011. For analytical work, certain types of inhibitor or proteinase were pre-absorbed from protein mixtures by modification of the method of Hejgaard et al (1981) to facilitate the identification of other types of inhibitors or proteinases.…”
Section: Affinity Chromatography Of Proteinases and Proteinase Inhibimentioning
confidence: 99%
See 1 more Smart Citation